Geochemical and isotopic studies of potassic granite from the western Dharwar Craton, southern India: Implications for crustal reworking in the Neoarchean. (22nd January 2021) - Sebastian, Sibin; Bhutani, Rajneesh; Balakrishnan, Srinivasan; Tomson, Joseph Kallukalam; Shukla, Anil Dutt
Abstract : The Neoarchean potassic granite from the Hosadurga region adjacent to the Chitradurga greenstone belt (CGB), part of the western Dharwar Craton (WDC), is studied for its petrogenesis. The combined field, petrographic, whole‐rock elemental, and Nd–Sr isotope data of granite and associated Tonalite–Trondhjemite–Granodiorite (TTG) gneiss from this region are presented here. The granites are alkali‐calcic to calc‐alkalic in terms of modified alkali lime index (MALI) and are weakly peraluminous (molar Al2 O3 /(CaO + Na2 O + K2 O) = 1.0–1.1). The geochemical data indicate that these are formed by the melting of TTG gneiss at depths above the garnet stability field. Isotopic data (εNd = −2.9 to −7.6 at T = 2, 600 Ma, ISr = 0.715–0.729, TDM  > 3.0 Ga) also show the involvement of Archean crustal sources. Trace element modelling was carried out using non‐modal equilibrium melting equation, which constraints partial melting of TTG source to a low degree (11%) for the formation of this granite. This model could also produce a major element composition consistent with this granite. The upper bounds on the magmatic temperatures (724–785°C) assessed from zircon saturation thermometry suggest that fluid influx is required. TTG samples show variable and very high positive epsilon Nd values (1.5–8.9), higher than the contemporaneous mantle, suggesting re‐melting of mafic crust. The observed high Nd isotope ratios in TTG indicate involvement of a mafic source that formed as early as ~3.8 Ga, probably as a result of global differentiation of the early Earth. Abstract : A Late Neoarchean potassic granite in the Western Dharwar Craton, having enclaves of older TTG, is shown to have formed by partial melting of TTG without significant mantle contribution. The TTG that formed at ~3.3 Ga must have been sourced from a mafic source as old as ~3.8 Ga.